White matter microstructure pathology in classic galactosemia revealed by neurite orientation dispersion and density imaging. Issue 2 (25th October 2014) - Timmers, Inge; Zhang, Hui; Bastiani, Matteo; Jansma, Bernadette M.; Roebroeck, Alard; Rubio‐Gozalbo, M. Estela
Abstract: White matter abnormalities have been observed in patients with classic galactosemia, an inborn error of galactose metabolism. However, magnetic resonance imaging (MRI) data collected in the past were generally qualitative in nature. Our objective was to investigate white matter microstructure pathology and examine correlations with outcome and behaviour in this disease, by using multi‐shell diffusion weighted imaging. In addition to standard diffusion tensor imaging (DTI), neurite orientation dispersion and density imaging (NODDI) was used to estimate density and orientation dispersion of neurites in a group of eight patients (aged 16–21 years) and eight healthy controls (aged 15–20 years). Extensive white matter abnormalities were found: neurite density index (NDI) was lower in the patient group in bilateral anterior areas, and orientation dispersion index (ODI) was increased mainly in the left hemisphere. These specific regional profiles are in agreement with the cognitive profile observed in galactosemia, showing higher order cognitive impairments, and language and motor impairments, respectively. Less favourable white matter properties correlated positively with age and age at onset of diet, and negatively with behavioural outcome (e.g. visual working memory). To conclude, this study provides evidence of white matter pathology regarding density and dispersion of neurites in these patients. The results are discussed in light of suggested pathophysiological mechanisms.